Impacto da capacitação em Boas Práticas de Fabricação na presença de Staphylococcus aureus e Escherichia coli em mãos e fossas nasais de manipuladores de panificadoras e confeitarias da região central de Goiânia-Goiás - SILVA, Ana Clara Martins e (2009)
The target of this study was to identify the presence of Escherichia coli and The aim of this study was to evaluate the impact of training in good manufacturing practices (GMP) in the presence of Escherichia coli and Staphylococcus aureus on hands and nasal cavities of food handlers of bakeries and confectioners, the central region of Goiânia, Goiás, Brazil. Samples were collected from hands and nasal cavities with sterile swab, 36 food handlers, 20 bakeries in the central region of Goiânia, two food handlers for each facility, clerk and baker before and one month after training in GMP. Check list was applied based on Resolution 216 in DRC, the National Health Surveillance Agency of the Ministry of Health, in bakeries and pre-test and post-test on GMP in defeat. Training on GMP for food handlers was given using two different methodologies, and application of traditional Arch of Maguerez. The bakeries and patisseries surveyed 90.0% were classified as unsatisfactory as the physical-functional, with risk of contamination of food. The hygiene of defeat was the main critical control point identified, as 90.0% of them are not trained to perform their functions, and ignore the principles of GMP. The correct post-test were higher than the pre-test with significant difference, indicating an increase of knowledge about GMP. There was no significant difference in learning for both methodologies applied. Prevalence of Staphylococcus aureus in the hands and nasal cavities was 13.5% and 11.1% before training and 5.5% and 22.2% after, respectively. The prevalence of Escherichia coli on hands and nasal cavities was 5.5% and 11.1% before and 0.0% and 5.5% after training, respectively. Reducing the prevalence of microorganisms after training and increased knowledge of GMP confirm the influence of training on improving hygienic and sanitary conditions